BUILDING DISTRIBUTED HETEROGENEOUS SMART PHONE JAVA APPLICATIONS AN EVALUATION FROM A DEVELOPMENT PERSPECTIVE (Journal of Information and Communication Technology, 2009)
The advances in mobile phone technology have enabled such devices to be programmed to run general-purpose applications using a special edition of the Java programming language. Java is designed to be a heterogeneous programming language targeting different platforms. Such ability when coupled with the provision of high-speed mobile Internet access would open the door for a new breed of distributed mobile applications. This paper explores the capabilities and limitations of this technology and addresses the considerations that must be taken when designing and developing such distributed applications. Our findings are verified by building a test client-server system where the clients in this system are mobile phones behaving as active processing elements not just mere service requesters.